2013 IEEE 56th International Midwest Symposium on Circuits and Systems (MWSCAS) 2013
DOI: 10.1109/mwscas.2013.6674661
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-integrated electrostatic energy harvesters

Abstract: Electrostatic-based power generation is an attractive alternative to piezoelectric and electromagnetic techniques, as it can be integrated in mainstream silicon technologies while providing higher power densities through miniaturization. However, at present, the power output of reported electrostatic micro-generators does not meet the communication and computation requirements of wireless sensor nodes. This paper presents an overview of electrostatic vibration-based energy harvesting. The challenges in designi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The novelty of this design lies in the combination of EEH configurations for a low-frequency oscillator and a high-frequency oscillator in a FupC strategy. Furthermore, the electromechanical design of EEHs requires the simultaneous consideration of both the mechanical and electrical behavior [32,33]. Investigation of conditioning circuits for various EEH configurations have resulted in several guidelines for a harvester's design [23] and operation [34].…”
Section: Introductionmentioning
confidence: 99%
“…The novelty of this design lies in the combination of EEH configurations for a low-frequency oscillator and a high-frequency oscillator in a FupC strategy. Furthermore, the electromechanical design of EEHs requires the simultaneous consideration of both the mechanical and electrical behavior [32,33]. Investigation of conditioning circuits for various EEH configurations have resulted in several guidelines for a harvester's design [23] and operation [34].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to MEMS devices employing variable capacitors with the mobile electrode vibrating in-plane, the out-of-plane structures can potentially achieve greater relative electrode displacement, which enhances performance, providing higher sensitivity in sensing applications [11] or power generation in energy harvesting [12]. Among all applications for MEMS variable capacitors, energy harvesting is attracting significant attention from MEMS research community [13][14][15], in the quest of providing power to wireless sensors by converting sound or mechanical vibration energy, which are broadly available indoor and outdoor [16,17]. The variable capacitor is alternatively charged and discharged during an oscillation period [18,19] and conversion of energy takes place when the charged capacitor's plates move against the electrostatic force attraction.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review on PZT-based energy harvesters has been reported by M. G. Kang et al [ 18 ]. While many studies have been performed on PZ devices, studies of ES devices that employed electret film have also drawn attention to improve device performance [ 19 , 20 , 21 , 22 ]. Y. Suzuki gave a comprehensive review in 2011, in which the details of electric power generation using the electret technique and progress up to that point are reported [ 3 ].…”
Section: Introductionmentioning
confidence: 99%